The Opinions of Classroom Teachers on Mathematics Learning Losses During the Pandemic Period - Aysel FERAH-OZCAN; Elife Nur SAYDAM (Anı Publishing, 2022)
This study aimed to determine the experiences of classroom teachers about learning losses in Mathematics during the pandemic period. This research, which was designed in the pattern of phenomenology, one of the qualitative research methods, was carried out with ten (10) primary school teachers working in different regions of Turkey in the spring term of the 2020-2021 academic year. As a result of the investigation, it was found that classroom teachers experienced that the presupposed skills of students with learning disabilities in mathematics are insufficient. In the teaching process, learning disabilities have negative effects in terms of learning and teaching, related to lack of knowledge and losses in mathematical learning areas, as well as emotional and social effects such as loss of self-confidence and emotional trauma in students. It has been found out that according to classroom teachers, the mathematics learning losses/deficiencies are explained by the sub-themes of student-environment, student-knowledge, subject and technical condition. Children's future academic achievement may be adversely affected due to losses/deficiencies. In the study, it is suggested to examine effects of learning losses/deficiencies with longitudinal studies.